Kepailitan Terhadap Anak Perusahaan dalam Holding Company Badan Usaha Milik Negara - Chintya Dewi Restyana S; Nikmah Mentari; Sri Eka Wulandari (Jurnal Hukum IUS QUIA IUSTUM, 2019)
Bankruptcy is a risk that can occur to both a subsidiary or a parent company in a state-owned holding enterprise. It is not a trivial matter for the state-owned holding company if its subsidiary suffers from bankruptcy, considering the position of the subsidiary and the parent company are separated, yet in some cases, the subsidiary is instead treated equally as a state-owned enterprise. The first issue would be, what is the legal relationship between the parent company and its subsidiary in the state-owned holding company; and second, how is the responsibility towards the bankrupted subsidiary. This research uses the normative juridical method. In which, it is concluded that first, as separate and independent entities, both the parent company and its subsidiary are restricted by the nature of separate legal entities and limited liabilities in carrying out their respective activities, even though they are bound under the same holding company. Second, the bankruptcy of a subsidiary of the state-owned holding company can occur and the responsibility of the parent company is limited to the shares that it owns, and if it is discovered that in its financial management, the parent company contribute in the bankruptcy of the subsidiary, then the responsibilities can expand.